THE RELATION LEVEL OF EDUCATION WITH KNOWLEDGE MOTHER PRIMIGRAVIDA TRISEMESTER III PREGNANCY ABOUT CHANGE DURING PREGNANCY IN BPM DEWI ISBAT COUNTRY SIDE MANJUNG DISTRICT NGAWEN SUB-PROVINCE KLATEN - Rucira Isthiantyari; Slamet Widodo; Siti Yulaikhah (STIKES DUTAGAMA KLATEN, 2015)
Background: Education has improvement impact degree of public prosperity. Public having education has ability to take choice or alternative and has is powered to increase degree of life, thereby public having level of relative education of height has opportunity larger ones to increase prosperity and would more can master science and eclectic. Purpose Of Research: To know relation between level of education with knowledge of mother primigravida trimester III about change during pregnancy in midwife Bidan Praktek Mandiri Dewi Isbat Manjung Klaten Tahun 2014. Research Method: This research type is analytic survey with approach of cross sectional. Population in this research mother primigravida trimester III in midwife Bidan Praktek Mandiri Dewi Isbat Manjung Klaten Tahun 2014. Instrument of Questionaire research, data analysis chi square. Result Of Research: That mother characteristic most of age 20 - 35 years, middle education and housewife work. Education mother most of is middle 17 (56,7%). Knowledge of pregnant mother about change during pregnancy most of enough 21 (70%). Conclusion: There is the relation level of education mother with knowledge of pregnant mother about change during pregnancy.